Strategy Analyst Improves Purchasing Decisions and Loyalty Through Brand Image, Life Style and Product Quality - ; Muh Abdul Aziz (Syntax Idea)
Technological progress refers to developments and innovations in the field of technology that result in significant changes in the way we live, work and interact. Technology continues to develop rapidly over time, and this affects various aspects of human life. Lifestyle, brand image, and product quality can all have an impact on a consumer's decision to buy an iPhone. The purpose of this study is to ascertain how lifestyle, brand image, and product quality influence Kota Sukabumi City residents' iPhone purchase decisions. A total of 150 respondents, the purposive sampling method, interview questionnaires, and structural equation modeling were all used in this study to collect data. In addition, the validity test, the reliability test, the correlation coefficient, the determination coefficient, the simple and multiple regression tests, the significance of the t-test, and the F test are utilized in this study. According to the findings of this study, these three variables; Lifestyle, brand image, and high-quality products all have a positive and significant impact on the iPhone brand's sales in Sukabumi City. In terms of lifestyle, this study suggests that a company should be aware of current trends and innovate its products to meet the needs of customers and maintain a positive brand image. Another suggestion is to offer a system that offers more benefits to its users. The final two, in terms of product quality, are producing batteries that last for a longer period of time and constructing mobile phones using a sturdy material. brand image, and high-quality products all have a positive and significant impact on the iPhone brand's sales in Sukabumi City. In terms of lifestyle, this study suggests that a company should be aware of current trends and innovate its products to meet the needs of customers and maintain a positive brand image. Another suggestion is to offer a system that offers more benefits to its users. The final two, in terms of product quality, are producing batteries that last for a longer period of time and constructing mobile phones using a sturdy material. brand image, and high-quality products all have a positive and significant impact on the iPhone brand's sales in Sukabumi City. In terms of lifestyle, this study suggests that a company should be aware of current trends and innovate its products to meet the needs of customers and maintain a positive brand image. Another suggestion is to offer a system that offers more benefits to its users. The final two, in terms of product quality, are producing batteries that last for a longer period of time and constructing mobile phones using a sturdy material. this study suggests that a company should be aware of current trends and innovate its products to meet the needs of customers and maintain a positive brand image. Another suggestion is to offer a system that offers more benefits to its users. The final two, in terms of product quality, are producing batteries that last for a longer period of time and constructing mobile phones using a sturdy material. this study suggests that a company should be aware of current trends and innovate its products to meet the needs of customers and maintain a positive brand image. Another suggestion is to offer a system that offers more benefits to its users. The final two, in terms of product quality, are producing batteries that last for a longer period of time and constructing mobile phones using a sturdy material.